Odpowiedzi

2010-04-12T21:19:45+02:00
A) 2x-x=-5-3
x=-8

b) -4x+3=-x-6
-4x+x=-6-3
-3x=-9
x=3

d) -x-2=x-9
-x-x=-9+2
-2x=-7
x=3.5

e) 2x-2=8
2x=8+2
2x=10
x=5

f) -2x+4-7=-5
-2x=-5-4+7
-2x=-2
x=1

g) 3x+4=-2x-1
3x+2x=-1-4
5x=-5
x=-1

h) -3x-6=9
-3x=9+6
x=-5
2010-04-12T21:57:01+02:00
A)2x+3=x-5
2x-x=-5-3
x=-8

b)-4x+3=-x-6
-4x+x=-6-3
-3x=-9 I:(-3x)
x=3

c)3x+3+2=-x
3x+x=-3-2
4x=-5
x=- 5/3=-1 i 2/3

d)-x-2=x-9
-x-x=-9+2
-2x=-7 I:(-2x)
x=7/2=3 i 1/2

e)2x-2=8
2x=8+2
2x=10 I:2
x=5

f)-2x+4-7=-5
-2x=-5-4+7
-2x=-2 I:(-2x)
x=1

g)3x+4=-2x-1
3x+2x=-1-4
5x=-5 I:5
x=-1

h)-3x-6=9
-3x=9+6
-3x=15 I:(-3x)
x=-5



/-ułamek